Senior Capstone at St. Mary’s College - Alexander, Susan (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course serves as a capstone course for your sociology degree. Each student will integrate the knowledge gained in her previous sociology courses in order to conduct an original project on a topic of her choosing. The final paper and oral presentation will demonstrate a student’s ability to apply and integrate the knowledge and analytical skills learned in her previous courses, such as research methods, social theory, and substantive area courses, such as statistics, gender, family, race and ethnicity, and/or social stratification.